METHOD OF TEACHING THE SUBJECT OF ADDING NUMBERS WITH DIFFERENT SIGNS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about the pedagogical skills and innovative approaches required of teachers to achieve high results in a short period of time in modern education. The importance of the use of pedagogical technologies and interactive methods for the effective conduct of mathematics lessons is analyzed. In particular, the methods used in teaching the subject of «adding numbers with different signs», including step-by-step and small group methods, are described in detail. The article explains the rules and examples of adding numbers with the same sign and different signs. Various games and practical exercises are offered to strengthen the subject. Also, a description of the «Three right and one wrong» method, which is used to determine and strengthen students’ understanding of the topic, is given. The article presents examples and problems based on the 6th grade mathematics textbook and highlights the effectiveness of modern pedagogical technologies. Recommendations are given to improve the effectiveness of the educational process using interactive methods.